Mental health and well‐being in parents of excessively crying infants: Prospective evaluation of a support package. (17th April 2018) - Powell, C.; Bamber, D.; Long, J.; Garratt, R.; Brown, J.; Rudge, S.; Morris, T.; Bhupendra Jaicim, N.; Plachcinski, R.; Dyson, S.; Boyle, E. M.; St James‐Roberts, I.
Abstract: Background: During the first 4 months of age, approximately 20% of infants cry a lot without an apparent reason. Most research has targeted the crying, but the impact of the crying on parents, and subsequent outcomes, need to receive equal attention. This study reports the findings from a prospective evaluation of a package of materials designed to support the well‐being and mental health of parents who judge their infant to be crying excessively. The resulting "Surviving Crying" package comprised a website, printed materials, and programme of Cognitive Behaviour Therapy‐based support sessions delivered to parents by a qualified practitioner. It was designed to be suitable for United Kingdom (UK) National Health Service (NHS) use. Methods: Parents were referred to the study by 12 NHS Health Visitor/Community Public Health Nurse teams in one UK East Midlands NHS Trust. Fifty‐two of 57 parents of excessively crying babies received the support package and completed the Edinburgh Postnatal Depression Scale and Generalized Anxiety Disorder‐7 anxiety questionnaire, as well as other measures, before receiving the support package and afterwards. Results: Significant reductions in depression and anxiety were found, with numbers of parents meeting clinical criteria for depression or anxiety halving between baseline and outcome. These improvements were not explained by reductions in infant crying. Reductions also occurred in the number of parents reporting the crying to be a large or severe problem (from 28 to 3 parents) or feeling very or extremely frustrated by the crying (from 31 to 1 parent). Other findings included increases in parents' confidence, knowledge of infant crying, and improvements in parents' sleep. Conclusions: The findings suggest that the Surviving Crying package may be effective in supporting the well‐being and mental health of parents of excessively crying babies. Further, large‐scale controlled trials of the package in NHS settings are warranted.